Strategies for minimizing nosocomial measles transmission. - Biellik, R. J. (World Health Organization, 1997)
As a result of the highly contagious nature of measles before the onset of rash, nosocomial transmission will remain a threat until the disease is eradicated. However, a number of strategies can minimize its nosocomial spread. It is therefore vital to maximize awareness among health care staff that an individual with measles can enter a health facility at any time and that a continual risk of the nosocomial transmission of measles exists. The present review makes two groups of recommendations: those which are generally applicable to all countries, and certain additional recommendations which may be suitable only for industrialized countries.